Pengembangan Media KASIBUM (Kartu Scan Interaktif Bagian Tumbuhan) Meningkatkan Literasi Sains Pada Kelas IV SD Negeri Sawentar 4: (The Development of KASIBUM (Interactive Scan Cards on Plant Parts) to Improve Scientific Literacy in Fourth Grade Students of SD Negeri Sawentar 4) - Nur Fitriyani, Della; Cindya Alfi, Cindya Alfi; Amalia, Shofi Nur (BIODIK, 2025)
The present study focuses on the development of KASIBUM (Interactive Scan Cards of Plant Parts), a learning medium designed to enhance science literacy among fourth-grade elementary school students. KASIBUM consists of printed cards embedded with QR codes that allow students to access educational videos when scanned. The development process followed the ASSURE model, which includes the stages: Analyze Learners, State Objectives, Select Methods, Utilize Media and Materials, Require Learner Participation, and Evaluate and Revise. The media underwent validation by both subject matter and media experts, feasibility testing by a classroom teacher, and effectiveness testing through a pretest–posttest design involving 16 fourth-grade students from SDN Sawentar 4. The validation results indicated high levels of validity, with scores of 88% from the subject expert and 96% from the media expert. The teacher's assessment also confirmed the media's high feasibility (96%). Furthermore, the average N-Gain score obtained from the pretest and posttest results was 0.81, which falls into the high category. In conclusion, KASIBUM is a valid, feasible, and effective medium for enhancing elementary students’ science literacy. Key words: KASIBUM, scientific literacy, learning media, plant parts, QR Code